50 Years of Communicating Demographic and Population Research in Germany - Johannes Huinink (Comparative Population Studies, 2025)
In his editorial, former CPoS editor Johannes Huinink reflects on his personal experiences with the journal as author, advisory board member and editor. He emphasizes the importance of scholarly debates, efforts to include contributions from the Global South, and shares his perspectives for the journal’s continued development and success. He focuses on both the ZfB and CPoS years. The ZfB played a key role in re-establishing demography as a scientific discipline in Germany. Since its relaunch in 2010 as CPoS, the journal has become an internationally recognized, English-language open-access platform with a strong focus on thematic Special Issues.